2017
DOI: 10.1159/000456707
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Apparent Diffusion Coefficient in Newborns with Hypoxic-Ischaemic Encephalopathy Treated with Therapeutic Hypothermia

Abstract: Background: Apparent diffusion coefficient (ADC) quantification has been proven to be of prognostic value in term newborns with hypoxic-ischaemic encephalopathy (HIE) who were treated under normothermia. Objectives: To evaluate the prognostic value of ADC in standardized brain regions in neonates with HIE who were treated with therapeutic hypothermia (TH). Methods: This prospective cohort study included 54 term newborns who were admitted with HIE and treated with TH. All magnetic resonance imaging examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
(34 reference statements)
2
11
0
Order By: Relevance
“…Importantly, chronic myelin disruption and associated axonopathy are apparent contributors to poor neurodevelopment after HIE, as shown by consistent correlation between microstructural lesions in the PLIC and frontal and parietal white matter, and mental, language and locomotor impairments. 7 , 26 , 29 Consistent with these reports, this study indicated modest reduction in MBP area fraction and structural tract integrity in parasagittal white matter at 7 days post-insult. Exploratory post-hoc tests suggested improvement to sham-ischaemic levels ( P = 0.06) in the first, but not second, parasagittal gyrus of rEpo-treated foetuses.…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, chronic myelin disruption and associated axonopathy are apparent contributors to poor neurodevelopment after HIE, as shown by consistent correlation between microstructural lesions in the PLIC and frontal and parietal white matter, and mental, language and locomotor impairments. 7 , 26 , 29 Consistent with these reports, this study indicated modest reduction in MBP area fraction and structural tract integrity in parasagittal white matter at 7 days post-insult. Exploratory post-hoc tests suggested improvement to sham-ischaemic levels ( P = 0.06) in the first, but not second, parasagittal gyrus of rEpo-treated foetuses.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple studies reported that lower apparent diffusion coefficient (ADC) values during the first 7–10 days were associated with adverse outcomes. This included lower ADC values in the basal ganglia [69, 72], the centrum semiovale [56, 70], the caudate nucleus [53], the PLIC [53, 56, 70, 71], the frontal or parietal WM [53, 70], and the posterior WM [56]. DWI of the thalami could be included in the meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Injury to the (posterior part of the) corpus callosum was related to adverse outcomes in 3 studies [53, 58, 68]. ADC values in the cerebellum and brainstem [70], as well as cortical ADC values [71], were not related to outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial spin labeling (ASL) has been validated as an effective noncontrast method for demonstrating perfusion deficits by demonstrating global hypoperfusion in BD with diffusely impaired cerebral blood flow on visual and quantitative analysis [ 16 , 17 ]. Diffusion weighted imaging (DWI) shows promise, and apparent diffusion coefficient (ADC) values obtained at high gradient strengths (b750–2000) have been shown to be helpful prognostic indicators in patients with HIE, with decreased ADC values predicting poorer outcomes [ 18 20 ]. Still, current use of high b-value DWI does not quantify perfusion and cannot be used to discriminate between the cellular injury of HIE and hypoperfusion related to BD.…”
Section: Introductionmentioning
confidence: 99%